Graphene metasurfaces biosensor for COVID-19 detection in the infra-red regime - Hussein A. Elsayed; Jacob Wekalao; Ahmed Mehaney; Haifa E. Alfassam; Mostafa R. Abukhadra; Ali Hajjiah; Wail Al Zoubi (Scientific Reports)
Abstract This study presents the design and analysis of a biosensor for COVID-19 detection, integrating graphene metasurfaces with gold, silver, and GST materials. The proposed sensor architecture combines a square ring resonator with a circular ring resonator, optimized through COMSOL Multiphysics simulations in the infrared regime. The sensor demonstrates exceptional performance characteristics, with absorption values exceeding 99.5% in the primary detection band (4.2–4.6 μm) and approximately 97.5% in the secondary band (5.0–5.5 μm). The device exhibits high sensitivity (4000 nm/RIU), a detection limit of 0.078, and a figure of merit of 16.000 RIU⁻¹ when utilizing crystalline GST as the substrate material. The sensor’s performance was further enhanced through machine learning optimization using XGBoost regression, achieving perfect correlation (R² = 100%) between predicted and experimental values across various operational parameters. The dual-band detection mechanism, combined with the integration of advanced materials and machine learning optimization, offers a promising platform for rapid, label-free, and highly sensitive COVID-19 detection. This research contributes to the development of next-generation biosensing technologies for viral detection and disease diagnosis.